INVISIBLE DISPLACEMENT: A CALL FOR COMPREHENSIVE LEGAL PROTECTION FOR "OTHER PERSONS OF CONCERN - Yatani, Vincent Godana (Sriwijaya Crimen and Legal Studies, 2023)
The global debate on forced migration, which focuses on international legal frameworks and policies, is subjugated mainly by the refugee narratives. The plight of displaced individuals who have been compelled to leave their homes but remain within their own country has received considerably less attention in the international arena due to the absence of a specific international legal framework that comprehensively addresses their unique challenges. These individuals, often generalized as "other persons of concern," attract little to no attention for protection and assistance from the global community. This research explores the legal protections currently available to "other persons of concern," and identifies gaps and challenges in these frameworks. The article analyzes existing literature on the subject, judicial decisions, and relevant legal instruments using the legal research method. The article argues for the urgent need to create a comprehensive legal framework that recognizes and protects the rights of "other persons of concern." Ultimately, this research makes a compelling call for the international community to recognize the vulnerability of "other persons of concern" and the pressing need to shift the discourse on forced displacement toward a more inclusive and comprehensive approach that recognizes the plight of all those who have been forcibly displaced, regardless of whether they have crossed an international border or not.